(untitled) (Journal of Asian Development Studies, 2024)
This research delves deeply into the upsurge of abusive language permeating our society, meticulously exploring its origins, manifestations, and ensuing repercussions. Through a systematic approach, interviews were conducted with students from Hazara University, unravelling the multifaceted facets of this linguistic phenomenon. The study discerns that the prevalence of abusive terms in everyday discourse is often rooted in varied intentions. Individuals employ such language as a means to establish camaraderie, assert dominance, alleviate personal frustrations, or, on occasion, as inadvertent slips. These motives underscore the complex interplay of social dynamics contributing to the proliferation of abusive language. Moreover, the research advocates for targeted interventions, particularly counselling, to assist individuals in managing their emotions effectively. By addressing the underlying emotional triggers, there exists the potential to mitigate the chronic use of abusive language. The emphasis on emotional regulation emerges as a critical component in steering societal discourse toward healthier and more constructive avenues. A pivotal finding of the study underscores the broader societal consequences of unchecked abusive language, particularly among older people. In essence, this research advocates for a nuanced understanding of the motives behind abusive language, coupled with targeted interventions aimed at emotional regulation. By addressing these aspects, society can aspire to cultivate a more respectful and harmonious discourse, mitigating the adverse effects on both interpersonal relations and broader societal peace.